2005
DOI: 10.1063/1.1920415
|View full text |Cite
|
Sign up to set email alerts
|

Atomically flat (110) SrTiO3 and heteroepitaxy

Abstract: We have prepared an atomically flat and insulating (110) SrTiO3 surface by annealing at high temperature under varying oxygen partial pressure. At low pressure, the polar surface is stabilized by oxygen vacancies, resulting in an atomically flat surface characterized by (110) unit-cell steps. The vacancies can be filled while maintaining this surface structure, providing an atomically ideal (110) substrate. We demonstrate two-dimensional homoepitaxial and heteroepitaxial growth, establishing the potential of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 21 publications
3
30
0
Order By: Relevance
“…This is in contrast to other reports 6,17 , where substrates treated at deposition conditions did not show any conductivity. However, similar low sheet resistance (5x10 -3  Ω/□) was recently reported in SrTiO 3 annealed at a low oxygen pressure of 5x10 -5 torr at 1000ºC 21 , which agrees with our data. They suggest that if the pressure is low enough, like 10 -6 mbar as for typical high-mobility LaAlO 3 /SrTiO 3 heterostructure depositions, even 800ºC is sufficient to reduce the SrTiO 3 .…”
supporting
confidence: 93%
“…This is in contrast to other reports 6,17 , where substrates treated at deposition conditions did not show any conductivity. However, similar low sheet resistance (5x10 -3  Ω/□) was recently reported in SrTiO 3 annealed at a low oxygen pressure of 5x10 -5 torr at 1000ºC 21 , which agrees with our data. They suggest that if the pressure is low enough, like 10 -6 mbar as for typical high-mobility LaAlO 3 /SrTiO 3 heterostructure depositions, even 800ºC is sufficient to reduce the SrTiO 3 .…”
supporting
confidence: 93%
“…On the other hand, for the case of LaAlO 3 /SrTiO 3 interfaces prepared on SrTiO 3 (110) substrate (Fig. 1c), both the SrTiO 3 and LaAlO 3 can be represented by planar stacks of (ABO) +4 and (O 2 ) −4 layers as proposed in Hwang et al 12 and Mukunoki et al 13 which leads to no polarization discontinuity at the interface. Consequently, no conductivity would be expected for such LaAlO 3 /SrTiO 3 (110) interfaces.…”
mentioning
confidence: 72%
“…We emphasize that the substrates were treated under oxygen-rich atmosphere. Mukunoki et al 21 recently reported that a strongly reducing atmosphere was required to obtain flat STO ͑110͒ surfaces when using substrates with a smaller miscut angle ͑ϳ0.1°͒ and wider ͑ϳ200 nm͒ terraces. The XRR data measured from a LCMO͑110͒ film are plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%